Branched thalamic afferents: What are the messages that they relay to the cortex? - (:unkn) unknown (ELSEVIER, 2011)
Many of the axons that carry messages to the thalamus for relay to the cerebral cortex are branched in a pattern long known from Golgi preparations. They send one branch to the thalamus and the other to motor centers of the brainstem or spinal cord. Because the thalamic branches necessarily carry copies of the motor instructions their messages have the properties of efference copies. That is, they can be regarded as providing reliable information about impending instructions contributing to movements that will produce changes in inputs to receptors, thus allowing neural centers to compensate for these changes of input. We consider how a sensory pathway like the medial lemniscus, the spinothalamic tract or the optic tract can also be seen to act as a pathway for an efference copy. The direct connections that ascending and cortical inputs to the thalamus also establish to motor outputs create sensorimotor relationships that provide cortex with a model of activity in lower circuits and link the sensory and the motor sides of behavior more tightly than can be expected from motor outputs with a single, central origin. These transthalamic connectional patterns differ from classical models of separate neural pathways for carrying efference copies of actions generated at higher levels, and introduce some different functional possibilities. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Efference copy; Corollary discharge; Sensorimotor link; Embodied perception; PRIMARY VISUAL-CORTEX; BRAIN-STEM TELLS; CORTICOTHALAMIC PROJECTIONS; CORTICOCORTICAL COMMUNICATION; DISTINGUISHING DRIVERS; SUPERIOR COLLICULUS; ACTION-POTENTIALS; FRONTAL-CORTEX; SINGLE-FIBER; RETROGRADE